The availability of training opportunities in personality disorders in American Psychological Association- and Psychological Clinical Science Accreditation System-accredited clinical and counseling psychology doctoral programs. - Levy, Kenneth N.; Ellison, William D. (Training & Education in Professional Psychology, 2022)
Personality disorders (PDs) are relatively common, especially in clinical settings. A number of evidence-based treatments are now available, especially for borderline personality disorder (BPD). However, little is known about the relevant training available to doctoral students in clinical and counseling psychology. In the current study, data were extracted from 336 clinical and counseling PhD and PsyD programs from the Insider's Guide to Graduate Programs in Clinical and Counseling Psychology (Sayette & Norcross, 2020), including the number of programs with faculty with specific interests in personality disorders and the number of programs with clinical opportunities related to personality disorders. We found that formal training in personality disorders is not widely available to most trainees in American Psychological Association (APA)-accredited doctoral training programs. Only 16% of programs have faculty with interests in personality disorders, all of them clinical psychology programs. PhD programs were more likely to have PD-interested faculty than PsyD programs, and, within clinical PhD programs, Psychological Clinical Science Accreditation System (PCSAS)-accredited programs were more likely to have PD-interested faculty than programs without PCSAS accreditation. Similarly, only 15% of programs (all clinical psychology programs) offer practicum opportunities in psychotherapy for personality disorders. Our findings indicate that doctoral-level psychology programs are not sufficiently preparing their students with personality disorder training, which serves as a substantial disservice to both trainees and the public.